1992
DOI: 10.1118/1.596757
|View full text |Cite
|
Sign up to set email alerts
|

Clinical dosimetry for implementation of a multileaf collimator

Abstract: In order to initiate the use of a multileaf collimator (MLC) in the clinic, a set of technical procedures needs to be available sufficient to create MLC leaf settings and to deliver an accurate dose of radiation through the MLC-shaped field. Dosimetry data for clinical use of the MLC were measured. Dosimetric characteristics included central axis percent depth dose, output factors, and penumbra. In this paper, it has been concluded that a dose control monitor unit calculation procedure that has been applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 0 publications
2
74
0
2
Order By: Relevance
“…The y-jaws are strategically placed at the upper and lower borders of the field. Figure 3 et al 25 and Klein et al 26 found that the tertiary MLC design is best treated as a block. That is, the equivalent square of the collimator field size is used.…”
Section: A2a Determination Of Field Size For S Cmentioning
confidence: 99%
“…The y-jaws are strategically placed at the upper and lower borders of the field. Figure 3 et al 25 and Klein et al 26 found that the tertiary MLC design is best treated as a block. That is, the equivalent square of the collimator field size is used.…”
Section: A2a Determination Of Field Size For S Cmentioning
confidence: 99%
“…Multileaf collimation (MLC) is standard in all modern linear accelerators used to treat patients 1 , 2 , 3 , 4 , 5 . The importance of rigorous quality assurance, especially with respect to the MLC and its impact on intensity‐modulated radiation therapy (IMRT) delivery, has been emphasized in the literature 6 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, integrated MLC systems with a 0.5 cm leaf width MLC have become commercially available. Some reports (1,2,3,4,5,6) have addressed the field edge penumbra obtained with 1.0 cm leaf width, compared to secondary collimation and alloy blocking. However the clinical field shaping advantages of the 0.5 cm leaf width over the larger leaf width have not been studied.…”
Section: Introductionmentioning
confidence: 99%